Synergizing Lean and Green Management for Sustainable Performance of Higher Education Institutions in Malaysia - Mohd Rizal Razalli; Rosman Iteng; Mohd Akhir Ahmad; Che Azlan Taib; Francis Chuah (International Journal of Supply Chain Management, 2020)
Despite the undeniable importance role of public universities in educating the Malaysian citizens, the universities these days are struggling to generate wealth for their own development. Generating wealth is becoming one of the important strategy for public universities as the allocation from the federal government for their operating expenditures has been drastically reduced. In fact, this strategy has been clearly outlined in the Malaysia Education Blueprint 2015-2025. Despite this significant reduction of source of income, the universities have to find a way to overcome this challenge by becoming more efficient and effective in their services to the stakeholders by becoming leaner. Lean universities will remove the existing waste or non-value added activities in many aspects in the universities' operations, which would yield higher returns and savings. In addition to lean, universities have also the responsibility to protect the environment. As a matter of fact, lean and green practices, share the same objective - that is to reduce waste. However, studies on lean and green universities is rather scarce. Even though there are evidences that these two concepts can be integrated, the synergy between the two concepts has yet to be discovered. This paper will elaborate on how lean and green can be integrated and the potential benefits towards sustainable higher education institutions performances.